1997
DOI: 10.1128/jvi.71.10.7478-7487.1997
|View full text |Cite
|
Sign up to set email alerts
|

Coreceptor usage of primary human immunodeficiency virus type 1 isolates varies according to biological phenotype

Abstract: The biological phenotype of primary human immunodeficiency virus type 1 (HIV-1) isolates varies according to the severity of the HIV infection. Here we show that the two previously described groups of rapid/high, syncytium-inducing (SI) and slow/low, non-syncytium-inducing (NSI) isolates are distinguished by their ability to utilize different chemokine receptors for entry into target cells. Recent studies have identified the C-X-C chemokine receptor CXCR4 (also named fusin or Lestr) and the CC chemokine recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(190 citation statements)
references
References 46 publications
3
184
2
1
Order By: Relevance
“…Recent very unexpected findings have indicated that chemokines and their receptors play pivotal roles in HIV infection. In addition to CCR5 and CXCR4, at least nine other chemokine or orphan receptors, including CCR2b, CCR3, CCR8, GPR1, GPR15, STRL33, US28, V28, and ChemR23, can function as coreceptors to support the cellular entry of one or more HIV strains into various types of cells [12][13][14]. Chemokines, such as macrophage inflammatory protein 1␣ (MIP-1␣), MIP-1␤, RANTES, monocyte chemotactic protein 2 (MCP-2), eotaxin, and SDF-1, have been shown to block the entry of certain HIV strains into its target cells by the corresponding chemokine receptors [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent very unexpected findings have indicated that chemokines and their receptors play pivotal roles in HIV infection. In addition to CCR5 and CXCR4, at least nine other chemokine or orphan receptors, including CCR2b, CCR3, CCR8, GPR1, GPR15, STRL33, US28, V28, and ChemR23, can function as coreceptors to support the cellular entry of one or more HIV strains into various types of cells [12][13][14]. Chemokines, such as macrophage inflammatory protein 1␣ (MIP-1␣), MIP-1␤, RANTES, monocyte chemotactic protein 2 (MCP-2), eotaxin, and SDF-1, have been shown to block the entry of certain HIV strains into its target cells by the corresponding chemokine receptors [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The conserved residues within the core of gp120 bind specifically to the coreceptors on different cell lines, an insight that offers us a way of viewing M-tropism versus T-tropism as being a mere matter of cells expressing CCR-5 or CXCR-4, respectively. Despite the previously mentioned controversies this approach is validated by the finding that for a variety of genetically diverse primary HIV-1 isolates, CCR-5 and CXCR-4 usage correlate with in vitro cytotropism for CD4 þ macrophages and T-cells [34][35][36]. In accordance with this a new consensus nomenclature has been proposed [37].…”
Section: Hiv Tropism and Entrymentioning
confidence: 97%
“…HIV-1 R5 and X4 variants exhibit different phenotypic characteristics in cellular tropism and replication ability [5]. Two viral proteins Gp120 and RT are closely associated with HIV-1 phenotypes since the former determines cellular tropism by specifically recognizing co-receptors and the latter determines viral replication ability.…”
Section: Positive Selection On Three Major Genes Gag Pol and Envmentioning
confidence: 99%
“…R5 and X4 have different viral characteristics, with R5 variants dominating the viral quasispecies early in and even throughout infection [1], whereas X4 variants classically emerge late in infection. X4 exhibits rapid replication and higher virulence in peripheral blood mononuclear cells (PBMCs) than R5 [5]. The emergence of X4 strains is usually accompanied by an accelerated decrease in CD4 + T cell counts, which leads to an accelerated disease progression [6].…”
mentioning
confidence: 99%